Peran dan Faktor-faktor yang Mempengaruhi Peran Lembaga Pemberdayaan Masyarakat Kelurahan (LPMK) dalam Pemberdayaan Ekonomi Masyarakat - Marda yulis (Jurnal Menara Ekonomi : Pelatihan dan Kajian Ilmiah Bidang Ekonomi, 2015)
The approach uses interpertatif approach. This approach is used because the localinstitutional review requires adequate interpretation to explain his role in theempowerment of society. Data analysis tool used in this research is descriptive qualitativeand descriptive statistics using the rating scale. The conclusions obtained from this study,LPMK role in the empowerment. Despite the fact that these local institutions actually havethe potential to empower communities. Internal factors which can encourage the role oflocal institutions in empowering, namely: a) Commitment of personnel agencies in the lineof duty, b) Funding agencies, c) The role of local institutions that have been standard, d)The experience of institutions in empowerment, e) competence contained in the institution,f) Means-infrastructure institutions, and g). The relationship between the agency personnel.While external factors, a) village government support, b) the support of other institutions,and c) government support for CityKeywords: Empowerment, LPMK